Autism Spectrum Disorder and Psychosis: A Case Study. Issue 2 (17th June 2016) - Cashin, Andrew
Abstract : PROBLEM: While apparently relatively common, there is often little clinician awareness of the risk of psychosis for people with autism. METHODS: A comprehensive review of the peer‐reviewed literature and a presentation of a case study. FINDINGS: There is a paucity of research available to determine the prevalence of the experience of psychosis in people with autism. CONCLUSION: There is significant boundary overlap between autism spectrum disorder and schizophrenia spectrum disorder. This article provides a comprehensive review of the research and a case study of a 16‐year‐old male with autism who experienced a brief reactive psychosis.